Effect of irrigation and tree density on vegetative growth, oil yield and water use efficiency in young olive orchard under arid conditions in Mendoza, Argentina - Trentacoste, Eduardo Rafael; Puertas, Carlos Marcelo; Sadras, Victor Oscar (2018)
We measured the effects of planting density (238, 317 and 476 trees ha−1), irrigation (fully irrigated control vs. deficit irrigation) and their interaction on the vegetative growth, yield and irrigation water use efficiency (IWUE) of young olive trees during three seasons. In the water deficit treatment, irrigation was applied when midday stem water potential (SWP) dropped below −2.5 MPa; SWP of controls was maintained between −1.2 and −1.5 MPa. Across irrigation treatments, oil yield at high density (968 kg ha−1) was 70 % higher than at low density. Reduction in oil yield due to deficit irrigation was not significant compared to control (501 vs. 664 kg ha−1). IWUE at lower tree density averaged 1.5 kg ha−1 mm−1, increased by 50 % in intermediate density and by 57 % at the highest density. Deficit irrigation increased IWUE twofold with respect to controls. IWUE responded to the interaction density × irrigation whereby the highest IWUE (4.6 kg ha−1 mm−1) was obtained at highest density and deficit irrigation. IWUE was nonlinearly related to seasonal water stress integral ( Sψ ), where maximum efficiency corresponded to 180 MPa days. The negative correlation between fruit water concentration and Sψ highlights the potential benefit of deficit irrigation of increasing oil extractability. The positive outcomes of increasing the density (higher oil yield) and deficit irrigation (higher IWUE, lower water concentration in fruit) need to be weighed against the long-term effect on vegetative growth. Under our conditions, three seasons of water deficit reduced crown and trunk size by 35 % in relation to fully irrigated.